Science and technology policy and the national innovation system in Argentina - Chudnovsky, Daniel (1999)
Looks at the strengths and weaknesses of the policies proposed in the Argintne National Multi-year Science and Technology Plan, 1998-2000, within the conceptual framework of the National Innovation System (NIS) approach.